Stakeholders' perspectives on the acceptability and feasibility of maternity waiting homes: a qualitative synthesis - Eva Julia van Braam; Daphne N. McRae; Anayda G. Portela; Jelle Stekelenburg; Loveday Penn-Kekana (BMC, 2023)
Abstract Background Maternity waiting homes (MHWs) are recommended to help bridge the geographical gap to accessing maternity services. This study aimed to provide an analysis of stakeholders' perspectives (women, families, communities and health workers) on the acceptability and feasibility of MWHs. Methods A qualitative evidence synthesis was conducted. Studies that were published between January 1990 and July 2020, containing qualitative data on the perspectives of the stakeholder groups were included. A combination of inductive and deductive coding and thematic synthesis was used to capture the main perspectives in a thematic framework. Results Out of 4,532 papers that were found in the initial search, a total of 38 studies were included for the thematic analysis. Six themes emerged: (1) individual factors, such as perceived benefits, awareness and knowledge of the MWH; (2) interpersonal factors and domestic responsibilities, such as household and childcare responsibilities, decision-making processes and social support; (3) MWH characteristics, such as basic services and food provision, state of MWH infrastructure; (4) financial and geographical accessibility, such as transport availability, costs for MWH attendance and loss of income opportunity; (5) perceived quality of care in the MWH and the adjacent health facility, including regular check-ups by health workers and respectful care; and (6) Organization and advocacy, for example funding, community engagement, governmental involvement. The decision-making process of women and their families for using an MWH involves balancing out the gains and losses, associated with all six themes. Conclusion This systematic synthesis of qualitative literature provides in-depth insights of interrelating factors that influence acceptability and feasibility of MWHs according to different stakeholders. The findings highlight the potential of MWHs as important links in the maternal and neonatal health (MNH) care delivery system. The complexity and scope of these determinants of utilization underlines the need for MWH implementation strategy to be guided by context. Better documentation of MWH implementation, is needed to understand which type of MWH is most effective in which setting, and to ensure that those who most need the MWH will use it and receive quality services. These results can be of interest for stakeholders, implementers of health interventions, and governmental parties that are responsible for MNH policy development to implement acceptable and feasible MWHs that provide the greatest benefits for its users. Trial registration Systematic review registration number: PROSPERO 2020, CRD42020192219.